Peran B Cell Activating Factor (BAFF) pada Penatalaksanaan Sindrom Nefrotik : Sebuah Paradigma Baru - Kristina, Astrid; Subandiyah, Krisni (Jurnal Klinik dan Riset Kesehatan, 2023)
Nephrotic syndrome is a glomerular disease characterized by severe proteinuria (≥3g/24 hours), hypoalbuminemia (≤25g/L), and oedema, with hyperlipidemia in some cases. This syndrome can affect both children and adults of all ages and can be caused by idiopathic or primary causes, or secondary causes due to infectious diseases, systemic diseases, malignancies, diabetes, and the effect of drugs. Specific therapy in nephrotic syndrome is determined by histopathology and the underlying cause. B cells or B lymphocytes are part of a key part of mammals' immune response called humoral immunity. Production of B cells in humans is lifelong, beginning in the fetal liver intrauterine and then in the bone marrow after birth. B cells developed from hematopoietic stem cells. The developmental stages of B cells include all stages of initial differentiation, maturation, antigen interaction, and ultimately antibody synthesis. Until recently, nephrotic syndrome was considered a T-cell-mediated disease, new insights point to the potential role of B cells in the pathogenesis of nephrotic syndrome. One of the mechanisms that occurs is that B cells produce antibodies that bind to antigens on the surface of podocytes which are special cells in the glomerulus and play a key role in the filtration process. In both SSNS and SRNS, the causal mechanism for both is still unclear but is thought to have a close relationship with immune system disorders, especially B cells.